Hubungan Lingkungan Kerja dan Konsep Diri dengan Burnout pada Anggota Brigade Mobile Kepolisian Daerah Sumatera Utara - Wayan Sugiarto; Sri Milfayetti; M. Rajab Lubis (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2020)
This study aims to determine the relationship between work environment and self concept with burnout. The study was conducted at the mobile brigade police of the Republic of Indonesia North Sumatra in the city of Medan. The number of respondents in this study were 196 members of the mobile brigade with non probability sampling techniques. Based on Spearman rank data analysis obtained a significant level between work environment (X1) with burnout (Y) with a significant value of 0,000 0,05, meaning that there is a partial relationship between work environment and burnout. While the relationship of self-concept (X2) with burnout (Y) with a significant value of 0,000 0.05. This proves that there is a partial relationship between self-concept and burnout. While the significance level of the work environment (X1) and self-concept (X2) with burnout (Y) with a significant value of 0,000 0,05 are related simultaneously, then the hypothesis in this study is accepted. The correlation between work environment and self concept with burnout on members of the mobile brigade in the city of Medan, North Sumatra is 56%.